(3QO GdeaJQi Yf GdWYf aj GdTTJQis - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s ((3eUWai Hf eMeO Hf eUWai s)
(3ChdgG (B:s
(3CeG HYO ajbhd TjNfG YHO GdZfi Hf ESeGYjd GdfGHdSi WdH efi HYV GdENhGf cJGHI TF HWQjb GdTQM dbUjOI GdYGQa HGddg GdTTJQi s
(3BNQgG (B:s
(3hdhHSWfG GdcdGe dWGd gPG GdGeQ hGSJYPH GdfGXQhf gPG GdNQe dcf ai gPG GdbOQ caGjI hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B556s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHOjQi HGdbOS s
Keywords: (3GdJUha hGdBOGH GdTQYjIs